The Radiation Impact of Solar Energetic Particle Events on the Moon: A Statistical Study Using Data‐Based Modeling Results - Bailiang Liu; Jingnan Guo; Yubao Wang; Mikhail I. Dobynde (Space Weather)
Abstract The Moon lacks a global magnetic field and atmosphere, leaving its surface been directly exposed to high‐energy cosmic radiation. Sporadic Solar Particle Events are sources of a significant radiation exposure, potentially posing serious threats to the health of astronauts exploring the Moon. In this paper, we use the Radiation Environment and Dose at the Moon (REDMoon) model based on GEometry And Tracking (GEANT4) Monte‐Carlo method to calculate the body effective dose induced by 262 large historical SEP events on the Moon under different shielding depths which can result from the lunar regolith shielding and/or additional aluminum shielding. We calculate and compare the contributions of different particles from or produced by SEPs to the total body effective dose. Additionally, we develop empirical functions to rapidly assess SEP‐induced effective dose on the Moon under different shielding scenarios.